Réponses

2014-03-19T17:17:28+01:00
B= (x+3(y+9) +10x - 7
   = xy + 9x + 3y + 27 + 10x -7
   = xy + 19x + 3y + 20

C= (3x-5)(7+6x) -(7+x)
   = 21x +18x²-35-30x - 7-x
   = 18x²-10x-42

D= 5x+1 -(x+4)(x-9)
 = 5x+1 -(x²-9x+4x-36)
= 5x+1-x²+9x-4x+36
= -x²+10x+37


A=3(x+2)+(7+4x)(7-6x)
   = 3x+6 +(49-42x+28x-24x²)
     = 3x + 6 + 49 - 42x + 28x - 24x²
= -24x² -11x +55

B=  4(x+9) -(7+x)(x+1)
   = 4x+36 -(7x + 7 +x² + 1)
   = 4x+36 -7x-7-x²-1
= -x²-3x+28

C=-2(1-3x) -(3x+2)(x-5)
   = -2-(-6x) -(3x²-15x+2x-10)
   = -2+6x -3x²+15x-2x+10
   = -3x²+19x+8

D= -3(a²+2) -(a-3)(2a+7)
   = -3a²-6 -(2a²+7a-6a-21)
     = -3a²-6-2a²-7a+6a+21
     = -5a²-a+15